Raltegravir use and outcomes among children and adolescents living with HIV in the IeDEA global consortium. Issue 7 (28th July 2020) - Patten, Gabriela; Puthanakit, Thanyawee; McGowan, Catherine C; Wools‐Kaloustian, Kara; Hazra, Rohan; Pinto, Jorge A; Machado, Daisy; Succi, Regina; Sohn, Annette H; Rabie, Helena; Musick, Beverly; Davies, Mary‐Ann; et al.
Abstract: Introduction: As integrase inhibitors become available in low‐ and middle‐income countries (LMICs), they offer the potential to expand extremely limited treatment options available to children and adolescents. In LMICs, only small numbers have used raltegravir, primarily as part of third‐line regimens. Using data from the IeDEA global consortium, we aimed to describe the characteristics of children on raltegravir‐containing regimens and their outcomes. Methods: We included data from 1994 to 2017 from children (age <18 years), from East and Southern Africa, Asia and South America, who received cART regimens containing raltegravir for ≥90 days. We describe their characteristics at raltegravir start, and their immunological and virological outcomes. Results and discussion: In total, 62 children were included, with median age at raltegravir initiation of 14.3 years (IQR 11.2 to 15.8) and median CD4 count of 276 cells/µL (IQR 68 to 494). Among 40 (65%) with drug resistance testing prior to raltegravir, 71% were resistant to at least one protease inhibitor (PI), and 32% had high‐level resistance to at least one drug class. Most (n = 50; 81%) received raltegravir as part of third‐line cART following PI‐based regimens, and were on regimens containing four or more drugs (n = 47, 76%). By database closure, median duration on raltegravir was 2.0 years (IQR 0.8 to 3.0), 1 (1.6%) patient had died, 6 (9.7%) were lost to follow‐up and 21 (34%) had discontinued raltegravir. Among 15 patients reporting reasons for stopping raltegravir, six discontinued because it was no longer available. Within one year of starting raltegravir, among 53 patients with VL measures, 40 (75%) had VL < 1000 copies/mL, and among 54 with a reported CD4 count, 45 (83%) and 36 (67%) were ≥350 and ≥500 cells/µL, respectively, with median CD4 count increasing to 517.5 cells/µL (IQR 288 to 810). Conclusions: Among children in LMICs, the initial use of raltegravir has been primarily for post PI‐based cART. We found good virological and immunological outcomes despite frequent prior triple‐class failure and high levels of drug resistance. Both access to raltegravir and long‐term adherence to regimens with large pill‐burdens remain challenging. Policies which promote earlier access to new drugs and simplify daily regimens for children and adolescents in LMICs are needed.